Administrative Services of the Faculty of Social Sciences in University of Dehasen Bengkulu for Students During the Covid-19 Pandemic - Dea Gusholianda; Evi Lorita; Yusuarsono Yusuarsono (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the Administrative Services of the Faculty of Social Sciences, Dehasen Bengkulu University to Students During the Covid19 Pandemic. This research uses qualitative research methods. The focus in this research is administrative services which are measured through the indicators of the Bengkulu Dehasen University Administration System in the Covid 19 Pandemic Period in Providing Services to Students. Methods of data collection using interview techniques, observation and documentation. Based on the research results, it is known that: (1) Tangibility (Direct Evidence): FIS buildings and rooms are good because they are neatly arranged, clean and beautiful. Providing services to students is carried out in a faculty room that has been given a glass partition or through a service locker. Where in the locker there is a notification regarding the prohibition for crowding, the 3M rule (wearing a mask, washing hands and keeping a distance). (2) Reliability: The reliability provided by the staff of the Faculty of Social Sciences, Dehasen Bengkulu University in providing administrative services to students during the COVID-19 pandemic is guided by the principles of efficiency and effectiveness. (3) Responsiveness: Responsiveness which is the principle of administrative services to students at the Faculty of Social Sciences, University of Dehasen Bengkulu, applies indicators: fast and timely service, and clear information delivery. (4) Assurance (Assurance and Certainty): The Faculty of Social Sciences, University of Dehasen Bengkulu, provides guarantees and certainty to students in providing administrative services. The guarantee and certainty referred to in this administrative service regarding the time and accuracy of the administrative services received by students. (5) Empathy (Attention): Employees/administrative staff at the Faculty of Social Sciences, University of Dehasen Bengkulu, are quick to respond and are responsive in providing information to all students who need administrative services with polite and friendly service.